Preservation mechanism of high concentration carbon dioxide controlled atmosphere for paddy rice storage based on quality analyses and molecular modeling tools. (January 2019) - Sun, Shuguo; Li, Beiping; Yang, Tao; Luo, Feijun; Zhao, Juanhong; Cao, Jianzhong; Lin, Qinlu
Abstract: Use of carbon dioxide controlled atmospheres has proven to be effective for the preservation of cereal grain during storage, but its preservation mechanisms remain to be fully elucidated. In this study, preservation mechanism of high concentration carbon dioxide controlled atmosphere for paddy rice storage was evaluated based on quality analyses and a novel method using molecular modeling tools. During 90 days storage, the fat acidity, cooked rice hardness, and lipoxygenase activity of paddy rice were gradually increased and alpha-amylase activity was decreased rapidly, but the degree of change of the paddy rice stored in controlled atmosphere was lower than that in non-controlled atmosphere. The rate constants for hydration water disaggregation from biological macromolecules, such as proteins and starch in paddy rice, and isothermal kinetic parameters were calculated according to simple first-order kinetics and the Arrhenius's law. The hydration water of paddy rice stored in non-controlled atmosphere presented the higher rate constant for degradation, especially at higher temperatures. Values of activation energies were 28.27 and 15.80 kJ/mol, respectively, for hydration water of paddy rice stored in controlled and non-controlled atmosphere. The mechanism of controlled atmospheres for paddy rice preservation may be the higher of activation energies for hydration water or biological macromolecules. Highlights: Mechanism of high concentration carbon dioxide controlled atmosphere storage for rice preservation was evaluated. First-order rate constants for hydration water disaggregation were calculated. Isothermal kinetic parameters were calculated according to the Arrhenius's law. Hydration water of paddy stored in high concentration carbon dioxide controlled atmosphere has higher activation energy.